Portal Wissen = Departure : The Research Magazine of the University of Potsdam - Zimmermann, Matthias; Mikulla, Stefanie; Kampe, Heike; Horn-Conrad, Antje; Lass, Sander; University Of Potsdam, Press (Universität Potsdam, 2022)
On October 20, 1911, the Norwegian Roald Amundsen left the safe base camp “Framheim” at the Bay of Whales together with four other explorers and 52 sledge dogs to be the first person to reach the South Pole. Ahead of them lay the perpetual ice at temperatures of 20 to 30 degrees Celsius below zero and a distance of 1,400 kilometers. After eight weeks, the group reached its destination on December 13. The men planted the Norwegian flag in the lonely snow and shortly afterwards set off to make their way back – celebrated, honored as conquerors of the South Pole and laden with information and knowledge from the world of Antarctica. The voyage of Amundsen and his companions is undoubtedly so extraordinary because the five proved that it was possible and were the first to succeed. It is, however, also a symbol of what enables humans to push the boundaries of their world: the urge to set out into the unknown, to discover what has not yet been found, explored, and described. What distinguishes science - even before each discovery and new knowledge – is the element of departure. Questioning apparent certainties, taking a critical look at outdated knowledge, and breaking down encrusted thought patterns is the starting point of exploratory curiosity. And to set out from there for new knowledge is the essence of scientific activities – neither protected nor supported by the reliable and known. Probing, trying, courageously questioning, and sensing that the solid ground, which still lies hidden, can only be reached again in this way. “Research is always a departure for new shoreless waters,” said chemist Prof. Dr. Hans-Jürgen Quadbeck-Seeger. Leaving behind the safe harbor, trusting that new shores are waiting and can be reached is the impetus that makes science so important and valuable. For the current issue of the University of Potsdam’s research magazine, we looked over the shoulders of some researchers as they set out on new research journeys – whether in the lab, in the library, in space, or in the mind. Astrophysicist Lidia Oskinova, for example, uses the Hubble telescope to search for particularly massive stars, while hydrologist Thorsten Wagener is trying to better understand the paths of water on Earth. Economists and social scientists such as Elmar Kriegler and Maik Heinemann are researching in different projects what politics can do to achieve a turnaround in climate policy and stop climate change. Time and again, however, such departures are themselves the focus of research: And a group of biologists and environmental scientists is investigating how nature revives forest fire areas and how the newly emerging forests can become more resilient to future fires. Since – as has already been said – a departure is inherent in every research question, this time the entire issue of “Portal Wissen” is actually devoted to the cover topic. And so we invite you to set out with Romance linguist Annette Gerstenberg to research language in old age, with immunologist Katja Hanack to develop a quick and safe SARS-CoV-2 test, and with the team of the Potsdam Center for Industry 4.0 to the virtual factory of tomorrow. And we will show you how evidence- based economic research can inform and advise politicians, and how a warning system is intended to prevent future accidents involving cyclists. So, what are you waiting for?! : Portal Wissen: The research magazine of the University of Potsdam [Englische Ausgabe]; 02/2021